2011
DOI: 10.1002/mop.25864
|View full text |Cite
|
Sign up to set email alerts
|

Size‐independent zeroth order electric plasmonic cavity resonator

Abstract: increased, the lasing spectrum is shifted from short to long wavelength with SMSR (Side mode suppression ratio) larger than 20 dB. The tuning range is measured to be about 40 nm with a maximum current of 42 mA. CONCLUSIONA hybrid-integrated tunable source, which is composed of an R-SOA and a polymer double-ring-resonator followed by a loopback mirror is proposed. The wavelength-selective reflector is fabricated with polymer materials of high-index contrast between core and cladding to allow the ring radius clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Using Equation (15) in Equation (13), the interaction constant with small imperfections in positioning of wires can be written as,…”
Section: Imperfections For a Uniaxial Wire Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…Using Equation (15) in Equation (13), the interaction constant with small imperfections in positioning of wires can be written as,…”
Section: Imperfections For a Uniaxial Wire Mediummentioning
confidence: 99%
“…The directive radiation characteristics of different type of antennas embedded in wire medium have been discussed in [8][9][10][11]. Also, the electromagnetic properties of a waveguide and cavity resonator filled with wire medium are studied by Nefedov and Viitanen [12] and Couture et al [13] respectively. The shielding properties of a wire medium slab in the long wavelength are studied by Lovat et al [14].…”
Section: Introductionmentioning
confidence: 99%
“…T HE concept of utilizing double-negative (DNG) metamaterial inclusions to render a resonator size-independent was introduced by Engheta [1]- [2] for a one-dimensional structure, to show that it is possible to build resonators that function independently of dimensions at those frequencies for which the metamaterial behaves as postulated. Three dimensional cavity resonators were investigated by Couture et al [3]- [4] and by Uslenghi [5]- [7].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of utilizing DNG metamaterial inclusions to render a resonator size-independent was introduced by Engheta [1]- [2] for a one-dimensional structure, to show that it is possible to build resonators that functions independently of dimensions at those frequencies for which the metamaterial behaves as postulated. This concept was later extended to fully three dimensional cavity resonators by Couture et al [3]- [4] and by Uslenghi [5]- [7]. Recently, Daniele et al [8]- [11] studied in detail a cylindrical resonator sectorally filled with metamaterial; in particular, their analysis showed that phase compensation leading to size independence is possible only if the cylinder is half-filled with metamaterial.…”
Section: Introductionmentioning
confidence: 99%